Enabling Social Innovation through Developmental Social Finance - Geobey, Sean; Westley, Frances R.; Weber, Olaf (Journal of Social EntrepreneurshipJournal of Social Entrepreneurship, 2012)
Abstract This paper explores social finance as a strategy for generating social innovations and, at the same time, financial returns. It explores why risk assessment for social finance is so challenging and suggests three sources of difficulty: setting boundaries, integrating heterogeneous values, and responding with sufficient speed and flexibility to support innovation. It suggests links between the seemingly distinct challenges of social finance being able to maximize its impact at different stages of the innovation process in a complex socio-ecological system, whilst also acting as a reframing agent in terms of the understanding of the system itself at other stages. Finally, this paper develops a new concept ?developmental impact investing? as a modified version of a portfolio strategy that uses a range of projects both to manage risk and to generate new knowledge about the complex systems in which the social finance attempts to create impact and innovation.